On the Powers of Dead-end Recognizing Systems in the Class of T wo-Element Sets Concerning Operations of ntersection and Complement - Vardanyan, Seyran M. (Mathematical Problems of Computer Science, 2021)
The notion of n-recognizing system in the class of two-element sets concerning the operations of intersection and complement is defined. The set of powers of dead-end n-recognizing systems of such kind is estimated.